The Association Between Knowledge and Foot Wound Prevention Behavior Among Patients with Type 2 Diabetes Mellitus at the Pasar Minggu Community Health Center - Tommy Jemmy Fransiscus Wowor; Retno Widowati; Firohmatin Firohmatin; Dea Aprilia (CV Media Inti Teknologi, 2026)
Background of study: Diabetes Mellitus is a chronic disease associated with various long-term complications, including diabetic foot wounds, which may lead to infection, lower-extremity amputation, disability, and increased mortality if not properly prevented. Effective prevention relies on patients' adherence to appropriate foot care practices, which may be influenced by their level of knowledge regarding diabetes and foot care.Aims and scope of paper: This study examined the association between knowledge level and foot wound prevention behavior among patients with Type 2 Diabetes Mellitus at the Pasar Minggu Community Health Center.Methods: A quantitative study with a cross-sectional design was conducted among 56 patients with Type 2 Diabetes Mellitus selected through total sampling. Data were collected using the Diabetes Knowledge Questionnaire (DKQ-24) and a foot wound prevention behavior questionnaire. Univariate analysis was performed to describe respondent characteristics, while the Pearson chi-square test was used to determine the association between knowledge level and foot wound prevention behavior.Result: Most respondents demonstrated a moderate level of knowledge (75.0%), while 64.3% exhibited a high level of foot wound prevention behavior. Statistical analysis revealed a significant association between the level of knowledge and foot wound prevention behavior (p = 0.016), indicating that respondents with higher knowledge levels were more likely to demonstrate appropriate preventive practices.Conclusion: Knowledge level was significantly associated with foot wound prevention behavior among patients with Type 2 Diabetes Mellitus. These findings highlight the importance of strengthening patient education on diabetic foot care to support preventive practices and reduce the risk of diabetes-related foot complications.